Collaborative research center for nanofluidics at Nazarbayev University - Ainabayev, A.; Berdenova, B.; Insepov, Z.; Tnyshtykbayev, K.; Aliyev, E.; Imanbayev, G.; Boguspayev, K.; Roshchupkin, D.V.; Kononenko, O.V.; Hassanein, A.; Bralts, V. (Nazarbayev University, 2013)
Our preliminary experiments conducted at NURIS, ICP, KazSU and IMT have discovered two new physical effects consisting of i) a significant increase of the rate of liquid pumping through a micron scale tubes under ultrasound irradiation; and ii) a considerable amplification of the magnitude of surface waves where a bias potential was applied to the surface of a graphene film deposited on piezoelectric material.
Keywords: first research week; innovative scientific research; nanofluidics